Strategies for the sustainable development of the PPP-based economic system - Babkin Alexandr; Semenov Alexandr; Babkin Ivan; Shkarupeta Elena; Mikhailov Pavel (BIO Web of Conferences, 2024)
The article is devoted to the implementation of public-private partnership (hereinafter - PPP) in modern Russia, which is forced to reorient its policy in the field of implementation of key PPP projects in order to maintain the focus on the strategy of implementing sustainable development in the economy. This problem is not covered in domestic literature and is extremely superficially touched upon in foreign literature, which determines the need for its consideration. The purpose of the work is to study data on the implementation of the PPP model in modern Russia with a focus on a sustainable development strategy. The key problem is the conclusion of transnational PPPs. Methods: analysis, synthesis, data comparison, formalization and generalization of key conclusions and proposals. The results provide an analysis of the likely comparison of data on transnational transactions concluded in the Russian Federation and their impact on the overall economic growth of the country. There are also suggestions for optimizing the further development of this area and its possibilities for optimizing the PPP model. The work includes the analysis of statistical data, as well as official information provided in open sources. In conclusion, an overview of possible publications and further research in the field of PPP and the development of sustainable development policy of the Russian economy is presented.